First Principles Calculations on Atomistic Mechanisms of Surface/Interface-Induced Properties and Database Construction (Communications in Computational Chemistry, 2025)
Surfaces and interfaces play a critical role in exploring novel chemical and physical properties because the interactionsbetween surface and adsorbents, as well as interfacial interactions, can be finely tuned by the interface configurations at the atomiclevel across a wide range, from strong covalent and ionic bonds to weak hydrogen bonds and van der Waals interactions. Theseinteractions enable precise control over molecular adsorption, self-assembly, and activation, facilitating the design ofnanostructures and modulation of novel properties. Recent developments in computational technologies, including high-throughput screening and machine learning, have significantly accelerated the discovery of functional materials. This reviewhighlights theoretical progress in manipulating the physical and chemical properties of organic molecules at surfaces andinterfaces, with a focus on controlling molecular configuration and magnetism, selective activation, on-surface synthesis, andinterfacial engineering of 2D materials. Our goal is to understand the key factors influencing the physical and chemical propertiesat surfaces and interfaces, with a particular focus on theoretical insights and computational approaches.
Keywords: surface chemistry; interface chemistry; computational simulation; 2D materials; molecular adsorption